If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x+6=5+3x+19
We move all terms to the left:
5x+6-(5+3x+19)=0
We add all the numbers together, and all the variables
5x-(3x+24)+6=0
We get rid of parentheses
5x-3x-24+6=0
We add all the numbers together, and all the variables
2x-18=0
We move all terms containing x to the left, all other terms to the right
2x=18
x=18/2
x=9
| m2-19m-150=0 | | 4x2-5x-4=0 | | 16-2=t+9+4t | | (2x+28)=(4x-2) | | Z2+10z=-9 | | y/5-1=3 | | (4x)=(8x) | | x/5+x/4=7/5 | | -77/55=k-55/8 | | X=5√x+9-2 | | 2/5x+4=4/5x-2 | | -39=6+9x | | 6n=9n-15 | | 0.18(y-9)+0.02=0.10-1.8 | | 176=11h-440/2 | | 3a+2=5a-10 | | 5(1+2m)=0.5(8=20m) | | 0.18(y-9+0.02=0.10y-1.8 | | 3a2+54=0 | | -5x-7x=-2x² | | 0=-19/5n | | 4j2-2156=0 | | -5x+8=15x+1 | | 8/5+3y=6y=1/5 | | 4m2+32=0 | | 9.2z+13.94=-16.83-8.9z | | 5y2-250=0 | | 9+2x+13=x+16 | | 15-20-12d=19-10d | | 2=3s | | 2x/3+1=25 | | 9x-(3x+2)=7x-13 |